2006
DOI: 10.1088/1126-6708/2006/10/061
|View full text |Cite
|
Sign up to set email alerts
|

Gravitino Dark Matter scenarios with massive metastable charged sparticles at the LHC

Abstract: We investigate the measurement of supersymmetric particle masses at the LHC in gravitino dark matter (GDM) scenarios where the next-to-lightest supersymmetric partner (NLSP) is the lighter scalar tau, or stau, and is stable on the scale of a detector. Such a massive metastable charged sparticle would have distinctive Time-of-Flight (ToF) and energy-loss (dE/dx) signatures. We summarise the documented accuracies expected to be achievable with the ATLAS detector in measurements of the stau mass and its momentum … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(122 citation statements)
references
References 46 publications
(65 reference statements)
1
121
0
Order By: Relevance
“…Being a metastable charged particle, it would have a distinctive experimental signature at the LHC or other colliders. Studies within such a scenario have shown that the mass of theτ 1 could be measured very accurately, and that one could easily reconstruct heavier sparticles that decay into theτ 1 [50]. Alternatively, the NLSP might be the lighter supersymmetric partner of the top quark, denoted byt 1 [51,52,53], which would have even more distinctive signatures at the LHC.…”
Section: Possible Supersymmetric Dark Matter Candidatesmentioning
confidence: 99%
“…Being a metastable charged particle, it would have a distinctive experimental signature at the LHC or other colliders. Studies within such a scenario have shown that the mass of theτ 1 could be measured very accurately, and that one could easily reconstruct heavier sparticles that decay into theτ 1 [50]. Alternatively, the NLSP might be the lighter supersymmetric partner of the top quark, denoted byt 1 [51,52,53], which would have even more distinctive signatures at the LHC.…”
Section: Possible Supersymmetric Dark Matter Candidatesmentioning
confidence: 99%
“…With measurements of the l 1 velocity β e l1 ≡ v e l1 /c and its momentum p e l1 ≡ | p e l1 |, m e l1 can be determined: m e l1 = p e l1 (1 − β 2 e l1 ) 1/2 /β e l1 [57]. For the upcoming LHC experiments, studies of hypothetical scenarios with long-lived charged particles are actively pursued [61,62,63]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [61], for example, it is shown that one should be able to measure the mass m e l1 of a (quasi-) stable slepton quite accurately at the LHC. The experimental determination of τ e l1 will be substantially more difficult than the m e l1 measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them will exit the interaction region appearing as "heavy muons." The slepton mass can then be determined from a combination of time-of-flight and momentum information [11][12][13]. Through ionization energy loss, a fraction of the produced sleptons will also be trapped inside the main detector [14,15] or in a separate stopper detector [2,16,17], where their decays can be precisely studied.…”
Section: Bbn and The Lhcmentioning
confidence: 99%